Conflict, insecurity and the political economies of higher education: The case of Syria post-2011. Issue 3 (30th November 2018) - Dillabough, Jo-Anne; Fimyar, Olena; McLaughlin, Colleen; Al-Azmeh, Zeina; Abdullateef, Shaher; Abedtalas, Musallam
Abstract : Purpose: This paper stems from a 12-month collaborative enquiry between a group of Syrian academics in exile in Turkey and academics from the University of Cambridge into the state of Syrian Higher Education after the onset of the conflict in 2011. The purpose of this paper is to draw on 19 open-ended interviews with exiled Syrian academics; two focus groups; mapping and timeline exercises; and 117 interviews collected remotely by collaborating Syrian academics with former colleagues and students who were still living inside Syria at the time of data collection. The findings of the research suggest that Syrian HE after 2011 was fragmented across regions; in some cases non-existent, and in others deemed to be in a state of reform in order to meet student needs. Key issues that emerged from this work are human rights' abuses directed against academics and students including the detainment, purging and kidnapping of academics, an increased militarisation of university life and a substantive loss of academic and human capital. Design/methodology/approach: The overall design involved two workshops held in Turkey (in June and July, 2017) at which the Cambridge team explained the stages of undertaking qualitative research and planned the collaborative enquiry with Syrian co-researchers. The first workshop addressed the nature of qualitative research and explored the proposed methods of interviewing, using timelines and mapping. The instruments for interviewing were constructed in groups together and mapping was undertaken with the 21 Syrian academics in exile who attended the workshop. Syrian academics also built their own research plans as a way of expanding the consultation dimension of this project inside Syria, engaged in survey and interview protocol planning and discussed ways to access needed documentation which could be drawn upon to enrich the project. The Syrian co-researchers interviewed remotely HE staff and students who had remained in, or recently left, Syria; the key criterion for group or participant selection was that they had recent and relevant experience of Syrian HE. The second workshop focused on data analysis and writing up. There was also wide consultation with participants inside and outside Syria. As part of the research, the Cambridge team conducted open-ended interviews with 19 Syrian academics and students living in exile in Turkey. This involved interviewing Syrian scholars about their experiences of HE, policy changes over time and their experiences of displacement. The researchers developed this protocol prior to the capacity-building workshops based on previous research experience on academic and student displacement, alongside extensive preparation on the conditions of Syrian HE, conflict and displacement. In addition to interviewing, a pivotal element of methodological rigour was that the authors sought to member check what participants were learning through mapping and timeline exercises and extensive note-taking throughout both workshops. The major issues that the authors confronted were ethical concerns around confidentiality, the need to ensure rigourously the protection of all participants' anonymity and to be extremely mindful of the political sensitivity of issues when interviewing participants who may not feel able to fully trust "outsider" researchers. Issues of social trust have been reported in the literature as one of the most significant drawbacks in conducting research in "conflict environments" (see Cohen and Arieli, 2011 ) where academics and students have been working and/or studying in autocratic regimes or were operating within political contexts where being open or critical of any form of institutional life such as university work or the nation could cost them their jobs or their lives. Findings: The accounts of Syrian academics and students emerging from this work point to some of the state-building expressions of HE manifested in the shaping of professional and personal experiences, the condition and status of HE, its spatial arrangements and their associated power formations, and resulting in feelings of intense personal and professional insecurity among Syrian scholars and students since 2011. While acknowledging that the Syrian situation is deemed one of the worst humanitarian crises in the region in recent decades, these accounts resonate, if in different ways, with other studies of academics and students who have experienced highly centralised and autocratic states and tightly regulated HE governance regimes (Barakat and Milton, 2015 ; Mazawi, 2011 ). Originality/value: Currently, there is virtually no research on the status and conditions of higher education in Syria as a consequence of the war, which commenced in 2011. This work presents a first-person perspective from Syrian academics and students on the state of HE since the onset of the conflict. The major contribution of this work is the identification of key factors shaping conflict and division in HE, alongside the political economies of HE destruction which are unique to the Syrian war and longstanding forms of authoritarian state governance.